2011
DOI: 10.1111/j.1741-2358.2011.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of denture adhesives on Candida albicans growth in vitro

Abstract: Objective: Denture-wearing favours the growth of Candida. In view of the fact that many denture wearers regularly use adhesives to enhance denture retention, stability and function, the aim of this work was to study the effect of denture adhesives on Candida albicans growth in vitro. Materials and methods: The denture adhesives tested were CoregaÒ powder and Corega Ò strip. C. albicans growth curves were obtained in the presence or absence of a 1% solution of the denture adhesive diluted in Sabouraud broth. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 40 publications
3
26
0
2
Order By: Relevance
“…The results also come in agreement with Gates etal and Maia etal (19,40) who investigated four denture adhesives and found that not only did each one contain fungal and bacterial contaminants, but also that each one could initiate fungal or bacterial growth when plated on the appropriate media. The percentages of plates exhibited growth were 66%, Some commercially available denture adhesives showed microbial contamination and some had significant inhibitory effect on C. albicans growth .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results also come in agreement with Gates etal and Maia etal (19,40) who investigated four denture adhesives and found that not only did each one contain fungal and bacterial contaminants, but also that each one could initiate fungal or bacterial growth when plated on the appropriate media. The percentages of plates exhibited growth were 66%, Some commercially available denture adhesives showed microbial contamination and some had significant inhibitory effect on C. albicans growth .…”
Section: Resultssupporting
confidence: 81%
“…. The Bonyplus (paste type 2)and Dentofix (paste type 1) contains methyl cellulose in their composition which is white granules, its viscosity increasing by the presence of organic salts (40) . This mean their viscosity increase in NaCl diluents solution and become less dissolve in dilution 1/10 and according to that become less affected by autoclave sterilization with less killing percentages.…”
Section: Resultsmentioning
confidence: 99%
“…This study also supported the findings of Sampaio-Maia et al . [14] where they found that among ten studied adhesives, four adhesives had an inducing effect on fungal growth while others had an inhibitory effect. In an in vivo study conducted by Oliveira et al .,[15] it was found that denture adhesives did not significantly alter the oral microbiota over a 14-day trial period, the results of which may have been influenced by the level of oral hygiene maintenance across different subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term use of adhesives may affect the oral microflora by selectively promoting the growth of some microorganisms and inhibiting others. The interactions between oral microorganisms and adhesives have been examined in vitro and in vivo . Some reports showed that adhesives did not have inhibiting or promoting effects on oral microorganisms Stafford and Russell reported that six tested adhesives (four powders and two pastes) plus sucrose could support growth of Streptococcus mitis and Candida albicans , whereas three in vitro studies revealed that some adhesives significantly inhibit C. albicans or oral malodor‐related microbes ( Streptococcus oralis , Streptococcus mutans, Prevotella oralis and Fusobacterium nucleatum ) growth.…”
Section: Introductionmentioning
confidence: 99%